Recovering user-interactions of Rich Internet Applications through replaying of HTTP traces - Salman Hooshmand; Gregor V. Bochmann; Guy-Vincent Jourdan; Russell Couturier; Iosif-Viorel Onut (Journal of Internet Services and Applications, 2018)
Abstract In this paper, we study the “Session Reconstruction” problem which is the reconstruction of user interactions from recorded request/response logs of a session. The reconstruction is especially useful when the only available information about the session is its HTTP trace, as could be the case during a forensic analysis of an attack on a website. Solutions to the reconstruction problem do exist for “traditional” Web applications. However, these solutions cannot handle modern “Rich Internet Applications” (RIAS). Our solution is implemented in the context of RIAs in a tool called D-ForenRIA. Our tool is made of a proxy and a set of browsers. Browsers are responsible for trying candidate actions on each DOM, and the proxy, which contains the observed HTTP trace, is responsible for responding to browsers’ requests and validating attempted actions on each DOM. D-ForenRIA has a distributed architecture, a learning mechanism to guide the session reconstruction process efficiently, and can handle complex user-inputs, client-side randomness, and to some extents actions that do not generate any HTTP traffic. In addition, concurrent reconstruction makes the system scalable for real-world use. The results of our evaluation on several RIAs show that D-ForenRIA can efficiently reconstruct user-sessions in practice.